Successful social media resistance: implications for employee voice. (2nd April 2020) - Walker, Michael
ABSTRACT: Industrial relations (IR) authors tend not to draw on critical management studies (CMS) literature. IR's radical wing believe it overstates the possibility of managerial control and IR's pluralist wing are disinterested because of their emphasis on institutions and processes. There is a need for pluralist industrial relations to make use of the research on resistance in CMS which has found social media to be capable of bringing about workplace change, meaning that it needs to be explained in pluralist IR as a form of voice. Informed by insights into successful social media resistance, a research agenda for IR is set out to extend our understanding of worker voice in the digital era.